Using a historical memoir to improve curriculum coherence in teacher education: The case of Trevor Noah’s Born a Crime (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
Two of the recurring concerns identified in teacher education are a lack of curricular coherence and a schism between content and practice. In this article, we discuss a specific intervention that was aimed at addressing these two challenges as they relate to English and History specifically. We argue that through the use of a carefully selected historical memoir, much tighter coherence between these subjects can be articulated in ways that facilitate students’ mastery of core concepts and skills across both these learning areas, as well as a richer appreciation of their implication for teaching practice. For the purposes of this article, we dene curricular coherence as an experienced sense of connectedness within and across modules. Focusing on the use of Trevor Noah’s memoir, Born a Crime (2016), we argue that engaging with a single historical text across multiple modules can improve curricular coherence and over a more integrated approach to engaging with wrien texts and historical resources. With close reference to the Department of Higher Education and Training’s Policy on the Minimum Requirements for Teacher Education Qualications, we reect on our experiences of integrating this memoir into an undergraduate Intermediate Phase (IP) teacher education programme at the University of Johannesburg (UJ). We show how this memoir was integrated into four modules that form part of the second year of the degree, namely English for the Primary School, Social Sciences for the Intermediate Phase, Teaching Methodology for English, and Teaching Methodology for the Social Sciences.
Keywords: Curricular coherence; English literature; Close reading; Teaching comprehension; Teaching literature; History education; Literary studies; Born a Crime; Primary school; Teacher education; Social Sciences; South Africa; Life writing; COVID-19